2009
DOI: 10.1095/biolreprod.108.075200
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Etv5 Decreases Proliferation and RET Levels in Neonatal Mouse Testicular Germ Cells and Causes an Abnormal First Wave of Spermatogenesis1

Abstract: Mice that are ets variant gene 5 (ETV5) null (Etv5(-/-)) undergo the first wave of spermatogenesis but lose all spermatogonial stem cells (SSCs) during this time. The SSC loss in Etv5(-/-) mice begins during the neonatal period, suggesting a role for ETV5 in SSC self-renewal during this period. Herein, we show that Etv5 mRNA was present in perinatal mouse testis and that ETV5 was expressed in fetal Sertoli cells and by germ cells and Sertoli cells during the neonatal period. Transplantation of Etv5(-/-) germ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 36 publications
2
64
0
Order By: Relevance
“…Regulation of early spermatogenesis by Sertoli cell signaling R161 expressed both in Sertoli cells (Chen et al 2005) and in SSCs (Oatley et al 2007, Tyagi et al 2009). Etv5-null germ cells fail to initiate spermatogenesis after transplantation into the testes of W/W v mice.…”
Section: Gdnf Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulation of early spermatogenesis by Sertoli cell signaling R161 expressed both in Sertoli cells (Chen et al 2005) and in SSCs (Oatley et al 2007, Tyagi et al 2009). Etv5-null germ cells fail to initiate spermatogenesis after transplantation into the testes of W/W v mice.…”
Section: Gdnf Signalingmentioning
confidence: 99%
“…Etv5-null germ cells fail to initiate spermatogenesis after transplantation into the testes of W/W v mice. Specifically, a positive feedback loop involving ETV5 and GDNF/RET/ GFRA1 regulates SSC self-renewal (Tyagi et al 2009). Interestingly, a recent study has suggested that ETV5 directly activates the expression of microRNA-21 to regulate the self-renewal of mouse SSCs (Niu et al 2011).…”
Section: Gdnf Signalingmentioning
confidence: 99%
“…Three additional GDNFregulated genes, basic helix-loop-helix family, member e 40 (Bhlhb2), homeobox C4 (Hoxc4), and Tec protein tyrosine kinase (Tec) were validated in rat SSCs (11). Among these six genes, Bcl6b and Etv5 have now been identified as important by several studies and appear to play a central role in rodent SSC self-renewal (10)(11)(12)(13). GDNF also regulates downstream signaling and ultimately rodent SSC maintenance and self-renewal, which involves phosphatidylinositol 3-kinase/serine-threonine kinase AKT family (PI3K/AKT), and Src family kinase (SFK) signaling mechanisms (14)(15)(16).…”
mentioning
confidence: 99%
“…Although there have been no definitive culture conditions for propagation of either mouse or human SSCs, culture systems established by different groups seem to be conducive for their propagation. At least in rodents, glial cell line-derived neurotrophic factor (GDNF) was found to be essential to maintain SSCs in an undifferentiated state in vivo and in vitro (Tyagi et al 2009;Hofmann 2008;Sariola and Immonen 2008;Oatley, Avarbock, and Brinster 2007;Naughton et al 2006;Kubota, Avarbock, and Brinster 2004;Meng et al 2000).…”
Section: Current Methods Of Isolation and Propagation Of Sscs With Emmentioning
confidence: 99%
“…Based on demonstrations of the importance of the stem cell niche (Tyagi et al 2009;de Rooij 2009;Hess et al 2006;Oatley, Racicot, and Oatley 2010), the pluripotential nature of SSCs and the instructive potential of various mesenchymes, we postulated and subsequently demonstrated that neonatal mouse SSCs could directly differentiate into prostatic, uterine and skin epithelium (Simon et al 2009) when recombined with the appropriate mesenchyme and grafted in vivo (Fig. 1).…”
Section: Spermatogonial Stem Cells Differentiate Into Tissues Of All mentioning
confidence: 99%